Konstruksi Realitas Perdamaian Antarkelompok Suporter Sepak Bola di Indonesia melalui Media Sosial: Studi pada Gerakan Mataram is Love di Platform Media Sosial X - Ferdian Angka Saputra; Sri Herwindya Baskara Wijaya (Jurnal Komunikasi Massa, 2025)
The rivalry between football supporter groups in Indonesia, particularly between Persis Solo and PSIM Yogyakarta supporters, has long manifested itself in various forms of hostility, both physical, symbolic, and cultural. However, the emergence of the Mataram is Love peace movement, which originated on social media platform X, marks a major shift by successfully fostering tangible peace between the two football supporter groups. This study aims to investigate the role of social media platform X in the Mataram is Love movement and to explore how peace as a tangible reality can be built by the Persis Solo and PSIM Yogyakarta supporter groups. This study uses a descriptive qualitative approach, focusing on digital posts and interactions on social media platform X related to the Mataram is Love movement. Data collection techniques include in-depth interviews with actors involved in the Mataram is Love movement and digital observation on social media platform X. The theoretical framework in this study is based on Peter L. Berger and Thomas Luckmann's, Theory of Social Construction of Reality. This theoretical framework is used to gain a deep understanding of how peace is built and strengthened both individually and socially. The results of the study show that social media X plays four main roles in the Mataram is Love movement: (1) facilitating open expression of aspirations for peace, (2) serving as a medium for information about the Mataram is Love peace movement, (3) facilitating interactive dialogue among individual supporters, and (4) bridging the transformation of digital action into collective action in the real world. These roles played by X support the process of constructing social reality through three dialectical moments formulated by Berger and Luckmann. In the externalization phase, supporters express their aspirations for peace through the X social media platform; in the objectification phase, symbolic acts of peaceful gatherings occur repeatedly, and external legitimacy support is established; finally, in the internalization phase, peace is accepted as a new social norm among the previously conflicting supporter groups.